Problem Case Historiography as an Alternative Learning Strategy to Train Historical Thinking Skills in The Merdeka Curriculum - Astutik, Winda Tri; Widiadi, Aditya Nugroho; Agung, Dewa Agung Gede; Wijaya, Daya Negri (Yupa: Historical Studies Journal, 2024)
The Merdeka Curriculum, which has just been implemented in Indonesia, still faces many obstacles in its implementation, especially in history subjects. This is because there are differences in the content and achievement of skills in the Merdeka Curriculum and the previous curriculum, namely the 2013 curriculum. One of the skill strands in history subjects is historical thinking skills. Based on the literature review conducted by the researchers, few learning strategies can be used specifically to train Historical Thinking Skills. For this reason, this research was conducted to provide alternative learning strategies that teachers can use to train students' Historical Thinking Skills. The method used in this research is the library method. The results of this study are in the form of a new learning strategy syntax called “Problem Case Historiography”. The use of this learning strategy is expected to be able to train students' Historical Thinking Skills.